2009
DOI: 10.1111/j.1440-1746.2008.05770.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic approach to regulate innate immune response by Toll‐like receptor 4 antagonist E5564 in rats with D‐galactosamine‐induced acute severe liver injury

Abstract: TLR4 antagonist E5564 reduced GalN-induced ALI in rats. It may contribute to the treatment of acute liver failure through blocking endotoxin-induced TNF-alpha overproduction of macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
(30 reference statements)
1
24
0
Order By: Relevance
“…In previous studies we found that Kupffer cells, part of innate immune system, produce a variety of cytokines known to be involved in the pathogenesis of cirrhotic liver [2], and Kupffer cells trigger the innate immune response through TLR4 in acute liver failure [15]. We also demonstrated that Kupffer cell phagocytic activity is reduced, but the innate immune response is enhanced, mediated by TLR4, in NASH [16].…”
Section: Discussionmentioning
confidence: 56%
“…In previous studies we found that Kupffer cells, part of innate immune system, produce a variety of cytokines known to be involved in the pathogenesis of cirrhotic liver [2], and Kupffer cells trigger the innate immune response through TLR4 in acute liver failure [15]. We also demonstrated that Kupffer cell phagocytic activity is reduced, but the innate immune response is enhanced, mediated by TLR4, in NASH [16].…”
Section: Discussionmentioning
confidence: 56%
“…(1) Lipid A mimetics (for example, E5564 and CRX-526 [150,151]) which bind to the TLR4-MD2 complex but lack intrinsic activity and thus prevent binding of the lipid A portion of LPS and subsequent TLR4 activation…”
Section: Future Prospectsmentioning
confidence: 99%
“…A phase II study in septic patients showed possible survival benefits in subgroups. Other investigators are studying its use for treating various other potentially TLR4 mediated conditions, e.g ., chronic LPS-mediated airway disease,17 liver disease,18, 19 contact lens-associated corneal inflammation,20 myocardial and renal ischemia-reperfusion injury21, 22.…”
Section: Eritoran Tetrasodiummentioning
confidence: 99%